2007
DOI: 10.3171/jns-07/07/0049
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and midterm follow-up results of using an electrodetachable, fully retrievable SOLO stent system in the endovascular coil occlusion of wide-necked cerebral aneurysms

Abstract: The fully retrievable self-expandible SOLO stent is a feasible, secure, and effective system with a high radial force and ease of delivery in treating wide-necked intracranial aneurysms in combination with coil embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 25 publications
1
31
1
Order By: Relevance
“…However, in our series, progressive occlusion rates (34 and 33 % of HydroSoft and bare coil, respectively) were lower than previous studies [44][45][46] and showed no significant difference among the two groups. The different results may due to anticoagulation therapies after embolization and different judgment criteria.…”
Section: Discussioncontrasting
confidence: 90%
“…However, in our series, progressive occlusion rates (34 and 33 % of HydroSoft and bare coil, respectively) were lower than previous studies [44][45][46] and showed no significant difference among the two groups. The different results may due to anticoagulation therapies after embolization and different judgment criteria.…”
Section: Discussioncontrasting
confidence: 90%
“…Twenty-seven papers [2][3][4][5]7,[9][10][11]13,[15][16][17][18]20,24,25,[28][29][30][33][34][35][36][37][38][39][40] , containing 736 patients, reported clinical follow-up of 13-month average duration and 6-month median duration. Twenty-one patients (3.2%) suffered delayed TIA/stroke in the territory subserved by the stented vessel.…”
Section: Clinical Follow-upmentioning
confidence: 99%
“…To date, clinical experiences with midterm follow-up results of different self-expandable stents have been reported [1][2][3][4][5] ; however, few reports exist in the literature publishing long-term data in regard to durability and long-term safety of these devices with or without comparison to other endovascular treatment techniques without the use of adjunctive stent placement. [6][7][8][9][10][11][12][13] In all these previous reports, the authors concur that stents have been associated with a significant decrease in angiographic recurrences.…”
mentioning
confidence: 99%